Kepemimpinan Strategis Dan Keberlanjutan UKM: A Systematic Literature Review - Yulia, Resi; Masdupi, Erni; Syahrizal (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
Research aim: The purpose of this paper is to identify and analyze some of the key literature on strategic leadership and SME coaching Approach: This paper is a Systematic Literature Review using the Science Direct database. Based on several stages in the systematic review method using the SPAR-4-SLR Protocol, 94 key articles from the Q1 category were found based on the Scimago Journal Ranking (SJR) Research Finding: This study found that 8 scientific groups support research on strategic leadership and SME sustainability Theoretical contribution: Many studies on SME sustainability have been carried out, but studies that look at the direct relationship of strategic leadership to SME sustainability are still very rare. Practitioner implication: This research provides more systematic knowledge and understanding for SME managers and academicians regarding improving SME sustainability related to their strategic leadership roles. Research limitation: This study also has limitations on the journal database, which is only sourced from Science Direct. The next study is expected to be expanded with other database sources such as scopus, Emerald, springer, and others for a more comprehensive study.